Linhas de orientação para uma alimentação vegetariana saudável - Silva, Sandra Cristina (2015)
Dietary patterns consisting exclusively, or mostly, of plant foods seem to have been common knowledge and followed since as far as the classical antiquity, essentially on philosophical and religious grounds, but also for health reasons. Over the last decades, alongside with an increase of knowledge on nutrition and environmental sciences, there has been an increment on scientific evidence in favor of a greater presence of plant foods in our diet. Populations showing high or exclusive consumption of plant foods seem to be less prone to develop chronic diseases, such as cardiovascular disease, certain types of cancers, diabetes and obesity. This dietary pattern, or 'diet', is not a uniform one, as it may consist solely of plant foods (strict vegetarian or vegan) but it can also include other elements such as eggs and dairy products (ovolactovegetarian). At its core there is usually fruit, vegetables, cereals, legumes, nuts and seeds, which should preferably be local ones, in season and minimally processed. The guidelines for a healthy vegetarian diet which are proposed in this document have been designed considering the healthy adult, which is why they should not be applied to other stages of a life cycle. The adequacy of this "diet" to the different stages of life, including childhood, adolescence, pregnancy, lactation, old age, and even to athletes, requires appropriate planning and monitoring. In order for this dietary pattern to be considered nutritionally adequate, factors such as the appropriate intake and bioavailability of certain nutrients such as protein, essential fatty acids, vitamin B12, vitamin D, iodine, iron, calcium and zinc and also caloric intake should be taken into account. Moreover, it is important to consider food diversity, the reduction in quantities of salt, sugar and saturated fats, and the adequate intake of water. In the case of vitamin B12, and due to the absence of nutritional sources in a vegan diet, it has to be provided through enriched foods or supplements. Although this food pattern is generally healthy and easy to adopt, particularly in countries like Portugal, where there is a varied and abundant offer of fruit, vegetables and other plant foods throughout the year, and where traditional cooking methods already include plant foods in their base, there is still considerable lack of information on the part of health and education professionals, associated with poor-quality information on online formats, a situation which this manual aims at improving.